2014
DOI: 10.1186/preaccept-1817458803126023
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell exosomes promote lung adenocarcinoma cell proliferation ¿ role of KIT-stem cell factor signaling

Abstract: BackgroundHuman cells release nano-sized vesicles called exosomes, containing mRNA, miRNA and specific proteins. Exosomes from one cell can be taken up by another cell, which is a recently discovered cell-to-cell communication mechanism. Also, exosomes can be taken up by different types of cancer cells, but the potential functional effects of mast cell exosomes on tumor cells remain unknown.Methods and resultsExosomes were isolated from the human mast cell line, HMC-1, and uptake of PKH67-labelled exosomes by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Furthermore, the transfer of TrkB may affect recipient cell signalling, since TrkB phosphorylation was upregulated in sh YKL-40 cells treated with pLKO exosomes. A similar mechanism has been reported with c-kit-containing exosomes that activate proliferation and PI3K dependent-signalling pathway [55]. Moreover, TrkB phosphorylation was slightly reduced by treatment of pLKO cells with sh YKL-40 exosomes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the transfer of TrkB may affect recipient cell signalling, since TrkB phosphorylation was upregulated in sh YKL-40 cells treated with pLKO exosomes. A similar mechanism has been reported with c-kit-containing exosomes that activate proliferation and PI3K dependent-signalling pathway [55]. Moreover, TrkB phosphorylation was slightly reduced by treatment of pLKO cells with sh YKL-40 exosomes.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, inhibition of functional rescue by K252a, a pan-Trk inhibitor [41], inhibiting TrkB activation, suggested that TrkB is implicated in these mechanisms, since TrkA was absent and TrkC was unchanged whatever cell types. TrkB mRNA expression level was unchanged in sh YKL-40 cells suggesting that the increase of TrkB receptor into sh YKL-40 cells is mainly due to its protein transfer through exosomes as already demonstrated with c-kit [55]. Furthermore, the transfer of TrkB may affect recipient cell signalling, since TrkB phosphorylation was upregulated in sh YKL-40 cells treated with pLKO exosomes.…”
Section: Discussionmentioning
confidence: 71%
“…Jan Lötvall (University of Gothenburg, Gothenburg, Sweden) reported on an emerging mechanism of micro-environmental cross-talk conducted via exosomes (40–100 nm in diameter) which are secreted by various cell types and play roles in epithelial-to-mesenchymal transition (EMT), tumor hypoxia, cancer invasiveness, metastasis, angiogenesis, and tolerance to chemotherapy (27). …”
Section: Microenvironment Metabolism Inflammation and New Conceptsmentioning
confidence: 99%
“…Tetraspanins, a family of transmembrane proteins (e.g., CD63 and CD81) are among the most abundant surface proteins on exosomes (Booth et al, ; Raposo & Stoorvogel, ) and are often used to quantify total exosome secretion. Exosome release has been demonstrated to increase by induced hypoxia (King, Michael, & Gleadle, ), DNA damage (Lehmann et al, ; Xiao et al, ), and by oxidative stress (Atienzar‐Aroca et al, ). However, not all pathological conditions may induce exosomal secretion.…”
Section: Exosome Release Mechanismsmentioning
confidence: 99%